2005
DOI: 10.1093/schbul/sbj078
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Functioning in Adolescents and Young Adults at Genetic Risk for Schizophrenia and Affective Psychoses: Results from the Harvard and Hillside Adolescent High Risk Studies

Abstract: Siblings and offspring of persons with schizophrenia carry elevated genetic risk for the illness and manifest attentional and memory impairments. Because less is known about other neuropsychological functions and their specificity in adolescents, we conducted a genetic high-risk (HR) study of schizophrenia (HR-SCZ) and affective psychosis (HR-AFF). Participants (ages 12-25) were from the Harvard Adolescent High-Risk and Hillside Family studies, including 73 HR-SCZ, 18 HR-AFF, and 84 community controls (CCs) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 88 publications
5
98
0
Order By: Relevance
“…Across all tests, lower performance during childhood predicted more prodromal symptoms in adolescence. This finding is entirely consistent with other VCFS research 47 as well as the non-VCFS schizophrenia research [70][71][72][73][74][75][76][77][78][79][80][81][82][83] . Thus, our data are entirely consistent with the extant non-VCFS high risk data; language and executive function deficits in childhood appear to presage which children with VCFS will develop significant prodromal psychotic symptoms in adolescence.…”
supporting
confidence: 91%
“…Across all tests, lower performance during childhood predicted more prodromal symptoms in adolescence. This finding is entirely consistent with other VCFS research 47 as well as the non-VCFS schizophrenia research [70][71][72][73][74][75][76][77][78][79][80][81][82][83] . Thus, our data are entirely consistent with the extant non-VCFS high risk data; language and executive function deficits in childhood appear to presage which children with VCFS will develop significant prodromal psychotic symptoms in adolescence.…”
supporting
confidence: 91%
“…Abuse and neglect are known to have a negative influence on cognitive functioning in community samples of healthy adults 20,21 and children/adolescents 22,23 as well as in patients with psychosis. 8,24,25 Congruent with other studies, [26][27][28] we have reported that children from densely affected multigenerational families who had a parent affected by schizophrenia or BD had fullscale IQ impairments as well as deficits in specific cognitive domains, such as visual and verbal episodic memory, working memory and executive functions of initiation. 12,16 These domains are among the most impaired in adult patients and are consistently found to be associated with schizophrenia and BD.…”
Section: Introductionsupporting
confidence: 52%
“…These impairments in genetic high-risk subjects are not confounded by psychosis or medications, and their presence in high-risk children and adolescents provided strong support for a neurodevelopmental model of pre-psychotic vulnerability for schizophrenia (49). There is substantial evidence that measures of sustained attention or vigilance, verbal declarative memory and working memory are valid endophenotypes in schizophrenia.…”
Section: Neurocognitive Endophenotypesmentioning
confidence: 93%